Multiple Gastric Erosion Early after a 3 V Lithium Battery (CR2025) Ingestion in an 18-Month-Old Male Patient: Consideration about the Proper Time of Intervention - Ioannis Patoulias; Christos Kaselas; Dimitrios Patoulias; Konstantinos Farmakis; Eleni Papacrivou; Maria Kalogirou; Thomas Feidantsis (Hindawi Limited, 2016)
Introduction. Button battery ingestion is considered an emergency situation in pediatric patients that needs to be managed promptly; otherwise, it may lead to serious and potentially lethal complications, especially when it is impacted in the esophagus. Less attention has been given in cases where the battery passes into the stomach, with guidelines for emergency intervention being based on the presence of symptoms. Case Report. We present a case of an 18-month-old male patient who presented to our emergency department after button battery ingestion. He did not have any symptoms and no pathological findings were encountered during clinical examination. X-ray investigation revealed the presence of the battery in the stomach. The patient was admitted for observation and two hours later he had two episodes of vomiting. He underwent urgent endoscopic removal of the battery where multiple acute gastric mucosal erosion in place of direct contact of the battery's negative pole with the mucosa of the gastric antrum was found. Conclusion. In specific cases the urgent endoscopic intervention for removal of an ingested button battery that is located in the stomach even in asymptomatic patients should be suggested.